Strategy And Optimization of the Role of Productive Waqf in People’s Economic Empowerment - Gatari, Altis Puspa; Zuhairoh, Saffaanah; Darokah, Husna Enggar Dani; Putra, Budi Jaya; Lubis, Ramadhona Amalia; Kurniawan, Mahrus Lutfi Adi (Journal of Islamic Economics and Philanthropy, 2025)
Waqf is an Islamic economic instrument that has great potential in supporting social and economic development. However, in Indonesia, waqf management is still not optimal, with most waqf assets not being utilized productively. This article analyzes the strategy and optimization of productive waqf in community economic empowerment, highlighting the challenges faced and innovative solutions that can be applied. The research method used is a literature study with a qualitative approach. The results show that effective strategies to maximize productive waqf include strengthening regulations, increasing the capacity of nadzir, integration with Islamic financial institutions, and implementing waqf-based business models. Case studies from various countries show that well-managed waqf can have a significant economic impact, including in the education, health and micro-enterprise sectors. This study concludes that with the implementation of appropriate strategies, productive waqf can be an important instrument in economic empowerment and improving the welfare of the community, as well as supporting sustainable economic development.